Antimicrobial activity of simplified mimics of celogentin C. Issue 12 (22nd March 2018) - Thombare, Varsha J.; Holden, James A.; Pal, Sreetama; Reynolds, Eric C.; Chattopadhyay, Amitabha; O'Brien-Simpson, Neil M.; Hutton, Craig A.
Abstract: Linear and bicyclic analogues of the peptide natural product, celogentin C, have been prepared in which the sidechain–sidechain crosslinks in celogentin are omitted or replaced with a mesitylenyl moiety. The simplified bicyclic peptides display moderate antibacterial activity, potentially through inhibition of bacterial protomicrotubule formation, while the linear analogs show higher antibacterial activity through a possible membrane disruption mechanism. Graphical abstract: